Perspectives on managing asthma and facilitators in asthma self-management among Thai school-age children: a qualitative study - Wipada Sangnimitchaikul; Boonjai Srisatidnarakul; Sigrid Ladores (College of Public Health Sciences, Chulalongkorn University, 2021)
Purpose - This study explored self-management in the context of asthma experiences of school-age children and the factors that facilitate asthma self-management. Design/methodology/approach - This is qualitative research used in-depth interviews. Purposive sampling was employed to select 15 school-age children with asthma attending the outpatient pulmonary department at university hospital in Thailand. Semistructured in-depth individual interviews were conducted. which were audiotaped and transcribed verbatim. Content analysis was used to analyze the data. Findings - Two major themes emerged from this study: (1) perspectives on managing asthma and (2) facilitators in asthma self-management. Four subthemes emerged from the first major theme related to views on managing asthma: (1) emphasizing use of an inhaler for asthma, (2) self-monitoring for symptom, (3) difficulties with the daily regimens and (4) family support on asthma self-management. Two subthemes emerged from the second major theme related to facilitators in asthma self-management: (1) confidence in performing asthma care behaviors and (2) asthma communication. Originality/value - This study described strategies that support asthma management of children in Thailand and provided insight into factors that influence asthma self-management. Findings will inform the development of future self-management interventions for school-age children with asthma.